LINGUISTIC AND CULTURAL FEATURES OF EMOTIONAL EXPRESSION IN ENGLISH AND UZBEK: A COMPARATIVE STUDY - Mirzayev Utkir Azamatovich, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article presents a comparative analysis of the means of emotional expression in English and Uzbek from both linguistic and cultural perspectives. Emotional expression plays a crucial role in human communication, as it reflects speakers’ attitudes, feelings, and cultural values. The study examines how emotions are conveyed through lexical choices, phraseological units, intonation, and stylistic devices in both languages. Special attention is paid to similarities and differences in expressing emotions such as joy, anger, sadness, and respect. The research also explores the influence of cultural norms and social conventions on emotional expressiveness, highlighting how English tends to favor more restrained and indirect emotional expression, while Uzbek often demonstrates greater emotional openness and expressiveness. By analyzing examples from everyday speech and written texts, the article aims to show how language and culture interact in shaping emotional communication. The findings of this study may be useful for linguistics students, language teachers, translators, and learners who are interested in cross-cultural communication and comparative linguistics.